Insulin-Like Growth Factor Axis and Gestational Diabetes Mellitus: A Longitudinal Study in a Multiracial Cohort - Zhu, Yeyi; Mendola, Pauline; Albert, Paul S.; Bao, Wei; Hinkle, Stefanie N.; Tsai, Michael Y.; Zhang, Cuilin (Diabetes (New York, N.Y.), 2016)
The insulin-like growth factor (IGF) axis may be implicated in glucose homeostasis, but its longitudinal profile across gestation in relation to the development of gestational diabetes mellitus (GDM) is largely unknown. We prospectively investigated IGF axis biomarkers in early-to-midpregnancy in relation to subsequent GDM risk in a case-control study of 107 case subjects with GDM and 214 control subjects without GDM, with blood sample collection at gestational weeks 10–14, 15–26, 23–31, and 33–39. Conditional logistic regression was used, adjusting for major risk factors including prepregnancy BMI. Plasma IGF-I and IGF binding protein 3 (IGFBP-3) concentrations and molar ratio of IGF-I to IGFBP-3 increased, whereas IGFBP-2 decreased throughout pregnancy. At gestational weeks 10–14, both IGF-I and IGF-I/IGFBP-3 were positively associated with GDM risk; adjusted odds ratio (OR) comparing the highest versus lowest quartile (ORQ4-Q1) was 2.93 (95% CI 1.18, 7.30) for IGF-I and 3.31 (1.10, 9.98) for IGF-I/IGFBP-3. In contrast, higher IGFBP-2 levels were related to a substantially lower risk of GDM (ORQ4-Q1 0.04 [0.01, 0.06]). Similar results were observed at gestational weeks 15–26. In sum, the IGF axis, IGFBP-2 in particular, may be implicated in the pathogenesis of GDM, with significant associations and incremental predictive value detected as early as gestational weeks 10–14, ∼10–18 weeks earlier before GDM is typically screened for.